Genome-Wide Identification and Characterization of Basic Pentacysteine Transcription Factors in Brassica napus - Huan Hu; Yuqin Jiang; Chiyuan Liu; Ying Zhang; Mingxun Chen; Zijin Liu (Plants)
BARLEY B-RECOMBINANT/BASIC PENTACYSTEINE (BBR/BPC), a plant-specific transcription factor family, is a group of GAGA_motif binding factors controlling multiple developmental processes of growth and response to abiotic stresses. BPCs recruit histone remodeling factors for transcriptional repression of downstream targets. However, the information about BnaBPCs from Brassica napus remains unclear. Here, we identified 25 BnaBPC genes that were mainly localized in the nucleus, randomly localized on 16 chromosomes, and grouped into three subfamilies based on phylogenetic analysis. Twenty-five BnaBPC genes exhibit syntenic relationships with AtBPC genes, and the polypeptides encoded by BnaBPC genes within the same subfamily share similar conserved motifs and protein domains. The expansion of BnaBPC genes underwent whole-genome duplication events and purifying selection in genomes, and all the BnaBPC genes had the same conserved GAGA binding domains. Additionally, the promoter of each BnaBPC gene consisted of various cis-elements associated with stresses, phytohormones, and growth and development. Notably, the seed-specific regulatory element was found only in the BnaC04.BPC4 promoter. Further expression pattern analysis showed that BnaBPC members are widely expressed in stems, buds, developing seeds and siliques. These findings provide insights into BnaBPC genes and enrich our understanding of their functional characterization in B. napus.